Welding today and tomorrow - Pilarczyk, J.; Zeman, W. (Автоматическая сварка, 2013)
It has been presented the huge changes in the Polish welding engineering which occurred in the last 20 years: in ownership among producers of welding equipment and materials, in investments which have been carried out, in the influence of free market, in the importance of knowledge and in the emerging of the people’s own potential. These factors enabled to decrease the distance between the Polish and world welding level.